Crypto tribunals: arbitration in the blockchain, with smart contracts and according to game theory - Santaolalla Montoya, Cayetana (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
There are authors in the doctrine who consider arbitration to be a conflict resolution mechanism, autonomous and independent of other state or judicial powers, to the point of considering it a non-national system for resolving commercial disputes. For them, arbitration lives on the margins, free and emancipated from any other power or order and subsists without respecting national legal frameworks, in the manner of delocalised arbitration. It was Rubellin-Devichi who, in 1965, put forward and defended this theory, and pointed out that arbitration could not be classified as exclusively contractual or jurisdictional, nor was it a mixed institution. Later, in 2005, Lew supported this doctrinal current and pointed out that arbitration should only be governed by international rules and practices, and not by national laws. This idea underpins the arbitration courts operating in the metaverse, combining blockchain, smart contracts and cryptocurrencies or tokens. Lew, Mistelis and Kroll point out that this theory will dominate arbitration in the future - can this be said?